A Training Monitoring System for Cyclist Based on Wireless Sensor Networks - N. M. Abdul Latiff; M. A. Ruslee; S. K. Syed Yusof; M. R. Abdul Rahim; H. Sayuti; K. Mohamad Yusof; M. A. Baharudin (Indonesian Journal of Electrical Engineering and Computer Science, 2017)
This paper presents a training monitoring system for cyclist that is based on the technology of wireless sensor networks (WSNs). A stable and reliable wireless cyclist monitoring system is vital to establish a smart and efficient sports management program. A training monitoring system has been developed and tested in a real cyclist training environment in a velodrome. The system is designed is such a way that the packet loss rate is minimum. Using TelG mote as the basis, customized sensor nodes that function as a forwarder node and the relay nodes are developed to form the WSN. This WSN is linked to the cloud network on the Internet. The cloud network is then established and end users application for data accessing is designed. Several experiments have been conducted in a real scenario in a velodrome to measure the reliability of the system architecture. It is shown from the experiments that the proposed system is reliable even when the cyclist is moving at a high speed. The packet loss is less than 2% which does not give a huge impact to the data transmission.